Efecto de los tipos de poda en especies maderables del Ecuador para mejorar la calidad comercial. - Garrido Quintero, Sara Noemí (2022)
Forest plantations of Alder (Alnus acuminata), Laurel (Cordia alliodora), Melina (Gmelina arborea), Pine (Pinus radiata) and Teak (Tectona grandis) in Ecuador have the objective of producing quality wood (free of knots). Pruning is a key activity to meet this objective, and its implementation should be analyzed from the beginning of the establishment of the plantation. In general, the main pruning activity is formation pruning or low commercial pruning, followed by high pruning, defining the technical requirements: timing (defined by the diameter over the stump ¨between 14-15 cm¨, if these values are exceeded, it complicates the work and limits the production of clear wood), the technique to be used (orientation pruning ¨thin branches¨ and staggered pruning ¨thick branches¨), the intensity (moderate pruning allows a better balance between growth and stem diameter, the optimum being to prune no more than 25%) and the amount of pruning (always depending on the natural pruning and the characteristics of the leaf system of each forest species). At the same time, they have an effect on the variables (continuous "diameter on stump, diameter of cylinder with defects" and qualitative "sociological position of the tree, damage to the trunk, quality of the tree and of the pruning") that indicate the quality of the treatment carried out. At the same time, the impact of pruning will be balanced with other management activities, especially thinning, which represents one of the actions based on the biological urgencies of the species